Evaluation of Independent Learning Curriculum Policies Implemented in Natural Schools in Indonesia - Taali , Muhammad; Darmawan, Arief; Maduwinarti, Ayun (International Journal of Social and Management Studies, 2023)
Nature school is a new concept in education that utilizes and protects nature for life as a medium for learning and character building. This study aims to evaluatively examine the curriculum in natural schools in accordance with the issuance of the independent learning program policy. This qualitative research uses a descriptive-explorative approach, and the analysis is carried out interpretively. The results of this study indicate that natural schools implement the 2013 curriculum which is integrated with the thematic curriculum which has been integrated with the religious education model in the teaching and learning process. In an evaluative process, the implications and outputs show that natural schools are better able to apply the principle of independent learning as a quality policy, whereas in public schools the principle of self-learning is reported to be still a formality and does not yet have measurable suggestions, due to the readiness of the education staff. This is what distinguishes the typical curriculum in natural schools which applies the principle of independent learning to the pattern applied in public schools. Researchers found that there was a development of program development interaction patterns in natural schools that absorbed the independent learning program, namely connecting between elements in each principle of achieving learning outcomes and their long-term impact.